Cannabidiol Administration Prevents Hypoxia-Ischemia-Induced Hypomyelination in Newborn Rats - Ceprián, María; Vargas, Carlos; García-Toscano, Laura; Penna, Federica; Jiménez-Sánchez, Laura; Achicallende, Svein; Elezgarai, Izaskun; Grandes, Pedro; Hind, William; Pazos, M. Ruth; Martínez-Orgado, José (Frontiers in Pharmacology, 2019)
Neonatal hypoxia-ischemia (HI) is a risk factor for myelination disturbances, a key factor for cerebral palsy. Cannabidiol (CBD) protects neurons and glial cells after HI insult in newborn animals. We hereby aimed to study CBD’s effects on long-lasting HI-induced myelination deficits in newborn rats. Thus, P7 Wistar rats received s.c. vehicle (HV) or cannabidiol (HC) after HI brain damage (left carotid artery electrocoagulation plus 10% O2 for 112 min). Controls were non-HI pups. At P37 neurobehavioral tests were performed and immunohistochemistry (quantifying mature oligodendrocyte [mOL] populations and myelin basic protein [MBP] density) and electron microscopy (determining axon number, size and myelin thickness) studies were conducted in cortex (CX) and white matter (WM). Expression of BDNF (brain derived neurotrophic factor) and GDNF (glial derived neurotrophic factor) were analyzed by western blot at P14. HI reduced mOL or MBP in CX but not in WM. In both CX and WM axon density and myelin thickness were reduced. MBP impairment correlated with functional deficits. CBD administration resulted in normal function associated with normal mOL and MBP, as well as normal axon density and myelin thickness in all areas. CBD’s effects were not associated with increased BDNF or GDNF expression. In conclusion, HI injury in newborn rats resulted in long-lasting myelination disturbance, associated with functional impairment. CBD treatment preserved function and myelination, likely as a part of a general neuroprotective effect.